Energy management in the embedded system - ANAD, Issa; FRIDJET, Salim; MGUERHI, Mohamed Elbachir; TLIBA, Abdenour (Echahid Hama Lakhdar University of Eloued, 2023)
"Abstract The energy management of an embedded system consists in controlling the energy flows of the different sources constituting the system. It makes it possible to satisfy the power demands of the load and increase the service life of the system while respecting various operating constraints such as the limited power of the sources, the states of charge of the storage elements, etc. For an ""Electric Vehicle"" application, we present in this work the energy management of an autonomous hybrid system composed of lead acid batteries used as the main source, super capacitors considered as an auxiliary source . Keywords: Embedded system, Energy management, Battery, Super capacitor, Electric" "تتمثل إدارة الطاقة في نظام مضمن في التحكم في تدفقات الطاقة للمصادر المختلفة التي تشكل النظام. يجعل من الممكن تلبية متطلبات الطاقة للحمل وزيادة عمر خدمة النظام مع احترام قيود التشغيل المختلفة مثل الطاقة المحدودة للمصادر، وحاالت شحن عناصر التخزين، إلخ. بالنسبة لتطبيق ""السيارة الكهربائية""، نقدم في هذا العمل إدارة الطاقة لنظام هجين مستقل يتكون من بطاريات الرصاص الحمضية المستخدمة كمصدر رئيسي، وتعتبر المكثفات الفائقة مصدرا مساعد"
مذكرة ماستر الكتروميكانيكdes thèses électromécanique
Keywords: "Keywords: Embedded system, Energy management, Battery, Super capacitor, Electric Vehicle."; الكلمات المفتاحية: نظام مدمج، إدارة الطاقة، بطارية، مكثف فائق، مركبة كهربائية.